Screening investigation of clinical and psychological manifestations of post-traumatic stress syndrome in combatants with optic trauma - Adbrakhimov, R. (Journal of Education, Health and Sport, 2018)
The objective: to make screening evaluation of post-traumatic stress syndrome in combatants with optic injuries to further optimize their medical and psychological support. Under the conditions of PIC 100 combatants were examined. 54 of them had optic injury with partial vision loss at the background of post-traumatic stress syndrome (PTSS) and 46 persons had symptoms of PTSS. Mental health of all the subjects was examined. For this they used the CAPS - scale and Neurotization and Psychopathization Questionnaire (NPQ). Use of CAPS –scale for screening allows to suspect symptoms of PTSS in the persons under examination. For their understanding and interpretation it is necessary to compare them with the data of clinical - diagnostic examinations. The use NPQ for screening with the aim to identify signs of psychological maladjustment among combatants and those with visual trauma fully satisfies the research. The established levels of neurotization and psychopathisation clearly demonstrate a shift in psychological maladjustment. Further research is advisable to direct to the development of a detailed study of the psychological state of persons with symptoms of post-traumatic stress disorder.